A Bibliometric Analysis of Digital Payment in Indonesian MSMEs - Ibnu Malik; Muhamad Juliardi (West Science Interdisciplinary Studies, 2023)
This paper collects articles using the Publish or Perish software, which includes the top 747 scientific articles indexed by Google Scholar from 2014 to 2023. The purpose of this paper is to analyze how digital payment articles are classified. Furthermore, to identify the research trends in digital payments, determine which research topics have the highest number of publications, and analyze future digital payment topics that provide opportunities for further investigation, All of these objectives are based on the research objectives of Indonesian MSMEs. In the context of this research, we conclude that public awareness regarding the use of digital payment services by MSMEs in Indonesia has been established. Based on the findings of this study, there are also specific issues that can be explored in more detail. Topics such as income, impact, and consumers provide opportunities for further research.